The impact of organizational changes towards employees’ performance at Northport (Malaysia) Bhd / Nuzul Najwa Nazree - Nazree, Nuzul Najwa (Faculty of Business and Management, 2018)
The purpose of the study was to investigate the impact of organizational changes towards employees’ performance at Northport (Malaysia) Bhd (NMB). Organizational changes which consist of communication, leadership, employee development and tolerance to change become the independent variables meanwhile employees’ performance becomes the dependent variable in this study. The research will be carried out with a sample size minimum of 335 employees from the total population of 2528 employees of NMB. In addition, the data that will be collected is by using a detailed structured questionnaire that must be answered by the respondents. Moreover, the researcher will use Proportionate Stratified Random (PSR) sampling method in order to gather the data from respondents. The data collected has been evaluated by using the Statistical Package for the Social Science (SPSS) version 21.0. Hence, Multiple Regression analysis indicated that there is a significant relationship between communication, leadership and tolerance to change with employees’ performance. However, no significant relationship between employee development with employees’ performance. Regression analysis also reveals that tolerance to change is the most influential factor towards employees’ performance at NMB.